Microfinance Institutions' Efficiency in the MENA region: a Bootstrap-DEA approach - Ines Ben Abdelkader; Salem Hathroubi; Mohamed Mekki Ben Jemaa (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
The purpose of this study is to evaluate the performance of microfinance institutions in The MENA region over the period 2006-2009. Following Simar and Wilson (1998, 2000) we use a DEA-Bootstrapping methodology to drift appropriate measures of DEA efficiency scores. The estimated results show that average efficiency of the most countries of the region has decreased over the period under study. Results also reveal that efficiency significantly differs by legal status of the microfinance institutions.
Additional information: A first draft of this paper has been submitted to the PS2D workshop held in Hammamet (Tunisia) and to the 12th Mediterranean meeting held in Sousse (Tunisia), both in june 2011.
Keywords: C14; G21; 330; Microfinance; DEA; Bootstrap; MENA; Microfinance; Data envelopment analysis; Bootstrap method; Middle East; North Africa